The potential impact of orange-fleshed sweetpotatoes on vitamin A intake in Sub-Saharan Africa. - Low, Jan W.; Walker, T.; Hijmans R.J. (International Potato Center, 2001)
A recent ex ante impact assessment indicates that orangefleshed sweetpotatoes can make a major contribution to alleviating vitamin A malnutrition in Sub-Saharan Africa. Replacing the white-fleshed varieties now grown by farmers with new high ß-carotene cultivars that meet local preferences would benefit an estimated 50 million children under age 6 who are currently at risk. The majority of children in Burundi, Rwanda and Uganda would benefit, as would about half of the children in Tanzania. Children in Ethiopia, Kenya and South Africa would also be affected, though to a lesser degree. The study did not take into account the benefits of the new cultivars to pregnant and lactating women, a population whose health is also likely to improve from the availability of the new plant types. Vitamin A deficiency is a major public health problem throughout the region and is responsible for tens of thousands of deaths annually among young children.